Why is chili hot? - Chemical notes on chili - Leidinger, Walter (2020)
The organoleptic analisis of capsicum or chili shows very interesting aspects of this native plant of the Andes from the chemical point of view. The variety of colours that are sinthesized by capsicum is surprising. Capsanthin and capsorubin generate a natural red colour with many uses in food. In regards to the odor, the aroma of chili is mostly determined by pyrazines with intense smell. Finally, capsicum stands out for a spicy taste due to capsaicin.